Hands-On .NET web API documentation with Swagger, OpenAPI (Packt Publishing, 2022)
A step-by-step approach to documenting an ASP.NET Web API project from scratch with Swagger/OpenAPI About This Video Understand the steps involved in documenting API with multiple versions by creating one document Learn the process of documenting an ASP.NET Web API project from scratch Explore various approaches available for documenting a web API, such as XML comments, data annotations, and more In Detail ASP.NET Web API is one of the hot topics in the ASP.NET world and many companies use APIs to connect front-end and back-end functionality at a large scale. What is the key element in such integrations? You need to document your web APIs so that they can be understood easily by developers. In this course, you will be learning about web API documentation using Swagger/OpenAPI concepts from scratch in this course. You will understand OpenAPI/Swagger and the need for documentation in web API. Learn the various approaches available for documenting a web API, including XML comments, data annotations, and so on. Also, we will use Swagger and Swagger UI tools from the OpenAPI community to create a rich API document. Then, create an OpenAPI document using Swashbuckle and NSwag in ASP.NET Web API. Learn how to use web API analyzers to guide you in including appropriate attributes for achieving complete documentation and web API conventions to automate and quickly document APIs with minimal effort. Next, understand the steps involved in documenting an API with multiple versions by creating one document per-version. By the end of this course, you will know how to document a web API project in ASP.NET Core using Swagger/OpenAPI from scratch. Audience This course is designed for backend web developers who want to build web services that are consumed by internal teams or external third-party teams. It is also useful for software architects who want to assist fellow developers to implement RESTful web API in their projects. For this course, one needs basic knowledge of building web API in ASP.NET Core and basic knowledge of OpenAPI/Swagger specification.